Tingkat Kepuasan Konsumen Terhadap Pelayanan Kefarmasian di Apotek 128 Kartasura - Aurella Novia Dewi Thalita Putri; H Hartono (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Patient-oriented pharmaceutical services (Pharmaceutical care) always pay attention to and focus on patient satisfaction. Services that focus on patient satisfaction are services that provide performance that is able to meet patient expectations. Pharmacy 128 Kartasura found several customer complaints that were dissatisfied with the services provided. This has an impact on consumers switching to other pharmacies. The purpose of this study was to determine the level of consumer satisfaction with pharmaceutical services at the 128 Kartasura pharmacy. This research is a descriptive study with a sample 120 respondents.The level of consumer satisfaction is measured using GAP analysis with the Servqual method and IPA (Importance Performance Analysis) method with Cartesian diagram analysis. The results showed that the level of satisfaction in the reliability dimension category (gap -0.32), the responsiveness dimension category (gap -0.16), the assurance dimension category (gap -0.14), the empathy dimension category (gap -0.21), tangible dimensions (physical evidence) category (gap -0.11). The conclusion of this study is the level of consumer satisfaction with pharmaceutical services at the 128 Kartasura Pharmacy in the quite satisfied category with a GAP value of -0.21. The 128 Kartasura Pharmacy needs to immediately make improvements to improve service to consumers, especially on the reliability aspect.